2012
DOI: 10.1016/j.ultrasmedbio.2012.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Ultrasound Imaging for Identification of Early Responder Tumor Models to Anti-Angiogenic Therapy

Abstract: Agents targeting vascular endothelial growth factor (VEGF) have been validated as cancer therapeutics, yet efficacy can differ widely between tumor types and individual patients. In addition, such agents are costly and can have significant toxicities. Rapid noninvasive determination of response could provide significant benefits. We tested if response to the anti-VEGF antibody bevacizumab (BV) could be detected using contrast-enhanced ultrasound imaging (CEUS). We used two xenograft model systems with previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 32 publications
5
40
0
Order By: Relevance
“…UMI has also proven its ability to detect biomarkers of early response to chemotherapy in several cancer types by MBs targeted to single biomarker expressions (VEGFR2, a V b 3 , endoglin, Annexin V, or VEGF-VEGFR complex) [24,[166][167][168][169] and MBs targeted to two or more of these biomarker expressions [142]. Impressively, studies have shown that UMI using a v b 3 -tMBs is a consistent method that can classify a tumour as a responder or a non-responder as early as two days after treatment [170,171]. To establish the link to clinical oncology Flisikowska et al [172] have suggested the use of larger animal cancer models with more similarities to humans, such as genetically modified pigs.…”
Section: In Vivo Molecular Imagingmentioning
confidence: 99%
“…UMI has also proven its ability to detect biomarkers of early response to chemotherapy in several cancer types by MBs targeted to single biomarker expressions (VEGFR2, a V b 3 , endoglin, Annexin V, or VEGF-VEGFR complex) [24,[166][167][168][169] and MBs targeted to two or more of these biomarker expressions [142]. Impressively, studies have shown that UMI using a v b 3 -tMBs is a consistent method that can classify a tumour as a responder or a non-responder as early as two days after treatment [170,171]. To establish the link to clinical oncology Flisikowska et al [172] have suggested the use of larger animal cancer models with more similarities to humans, such as genetically modified pigs.…”
Section: In Vivo Molecular Imagingmentioning
confidence: 99%
“…7 The size of these microbubbles (generally 1-8 µm) makes them excellent blood pool agents for visualization of blood flow in vessels within the tumor. [7][8][9] Ultrasound contrast agents (UCAs) have been widely used to monitor treatment response in both humans [9][10][11][12] and animal models of cancer, 13,14 but investigations have mainly focused on changes in either fractional blood volumes or blood flow kinetics as an indicator of treatment response relative to tumor size. Targeted UCAs have been described in which a targeting ligand is used to increase the affinity of the microbubble to the site of marker expression with promising results, but such UCAs are not currently approved for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Not only new compounds are tested but also novel drug delivery methods, such as silk gel to effectuate a sustained release of chemotherapeutics locally [100] . Ultrasound visualization is being used for more accurate tissue implantation, as well as identifying early response to treatment [101,102] .…”
Section: In Vivo Modelsmentioning
confidence: 99%